2015
DOI: 10.1161/circresaha.116.303697
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Immunity, and Hypertensive End-Organ Damage

Abstract: For more than 50 years, it has been recognized that immunity contributes to hypertension. Recent data have defined an important role of T cells and various T cell-derived cytokines in several models of experimental hypertension. These studies have shown that stimuli like angiotensin II, DOCA-salt and excessive catecholamines lead to formation of effector like T cells that infiltrate the kidney and perivascular regions of both large arteries and arterioles. There is also accumulation of monocyte/macrophages in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
478
2
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 582 publications
(510 citation statements)
references
References 97 publications
17
478
2
13
Order By: Relevance
“…Currently, no drugs are available to accomplish this latter goal. 10 In addition, vaccines could be a therapeutic option for prevention or treatment of arterial hypertension.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, no drugs are available to accomplish this latter goal. 10 In addition, vaccines could be a therapeutic option for prevention or treatment of arterial hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] This seminal work has caused great interest in the immunologic aspects of hypertensive disease. [7][8][9][10] This review will give a brief overview of the components of the innate and adaptive arm of the immune system in hypertension and summarize recent advances in immunologic research, with a special focus on their potential relevance for hypertension and hypertensive endorgan damage. Very recent findings on the role of dendritic cells as well as CD8…”
mentioning
confidence: 99%
“…Increasing evidence indicates that adaptive immunity and innate immunity play a key role in the pathogenesis of hypertension and in the associated end-organ damage (60). Pioneering studies in lymphocyte-deficient mice (Rag1 -/-mice) established that T lymphocytes are required for the BP elevations in several hypertension models (61).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the metabolic disorder in the liver is the background for the development of chronic inflammatory process of low severity [33]. It is shown that it is non-specific systemic inflammation that brings together into a unitary syndrome hypertension, increased body weight (especially abdominal obesity), dyslipidaemia and atherogenesis [81]. Significant (p < 0.001) increase in inflammation markers (TNF-a, IL-1, IL-6) and increase (p < 0.001) in the circulating immune complexes' level were identified in patients with comorbidity (a combination of hypertension, obesity and NAFLD [75].…”
Section: Nonspecific Systemic Inflammationmentioning
confidence: 99%